PENGARUH METODE MENGAJAR DENGAN MENGONTROL MOTIVASI TERHADAP PRESTASI BELAJAR - Muhammad Ali Gunawan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
The aim of this research is to find out: The difference of learning achievement  between students who is taught using inquiry method and others who use task-based method and direct method using media in the Mathematic Statistic I subject in Mathematics Education Program Pekalongan University after controlling using motivation variable. The research is done towards all fifth semester students which are 114 people (30 people IV A class, 36 people IV B class and 48 people). Data analysis used is covariant analysis (ancova 1 line). The result of this research showed that: 1) after controlling by motivation variable, there is  the  difference  of  learning  outcome  between  students  who  is  taught  using  inquiry method and others who use task-based method and direct method using media. Where the result from covariant analysis showed the significance 0,000 less than α = 0,05 which is determined;  2)  after  controlling  by  motivation  variable  ,  students  who  is  taught  inquiry method  is  77.69  better  than  students  who  is  taught  direct  method  using  media with  the score of learning outcome in 67,95 better than the students who is taught by using task- based method with the score in 62,29.